An outline of psychoanalysis - Van Teslaar, James S. (James Samuel) 1886- (Modern Library, 1925)
"Perhaps the multitude of feature articles in our newspapers and periodicals and of books aiming to popularize psychoanalysis denotes a widespread interest and ought to be welcomed. But so many incorrect views float about and so many absurd inferences, wrongly attributed to psychoanalysis, find ready acceptance, on this point, that the practicing psychoanalyst and earnest student finds this state of things far from satisfactory, notwithstanding the apparent popularity of the subject. This volume collects in one place the important (and perhaps the defining) contributions by the founders and pioneers of psychoanalysis. The chief contribution of psychoanalysis, aside from its special hypotheses and doctrines, is the viewpoint it introduces in the investigation of mental processes. Psychoanalysis represents a logical extension of the evolutionistic theory. It has inaugurated the application of the principle of evolution to the explanation of mental processes. Henceforth the approach of any problem in which human nature plays a role must include a careful consideration of the developmental aspects of the mind of man. Conversely, psychoanalysis has taught us that a consideration of the evolutionary or developmental aspects of the mental processes holds the key to the understanding of problems in which human nature plays a role. The adaptation of the developmental viewpoint to mental phenomena, then, is the chief--the permanent--contribution of psychoanalysis to the growth of human knowledge"--Introduction.